HUBUNGAN MOTIVASI PERAWAT DENGAN KEPATUHAN PELAKSANAAN STANDAR PROSEDUR OPERASIONAL PENCEGAHAN RISIKO JATUH DI RUANG RAWAT INAP - Ahsan Ahsan; Niko Dima; Ni Luh Putu Ayu Prasiska (Jurnal Kesehatan Mesencephalon, 2018)
Falling is a serious problem and makes high costs for patients and all health facilities. One of the factors that influenced the compliance of the Nurses in the implementation of the SPO (Operational Procedure Standard) is the motivation and perception of the Nurse toward their profession. The aim of the research is to find out the relationship between Nurses motivation and compliance with the implementation of the prevention risk proedure. This study was used a cross-sectional design. The population used is all nursing staff in the inpatient ward of Kanjuruhan Hospital with purposivei sampling technique with a sample of 109. The study was conducted in February - March 2018. Data collection used questionnaires about the characteristics of respondents, nurses' motivation and compliance with risk prevention procedure of fall down. Statistical analysis uses Ranki Spearman test. Presentation of data in the form of frequency tables distribution and narration. The results of the study were found that is significant relationship between motivation and compliance with the implementation of preventive SPO at risk of falling. The correlation (r) value is 0.424 which means that the relationship between the two variables are in the same direction, the higher the motivation, the compliance with the implementation of the preventive SPO become higher too. From the results of this study, a continuous socialization of SPO prevention is needed, and make motivated nurses to comply with the implementation of the SPO.Keywords: Risk of falling, Standard Operating Procedure, Compliance, Motivation